Hubungan Pengalaman dan Lama Rawat dengan Kecemasan pada Anak yang Menjalani Hospitalisasi di Ruang Rawat Inap RS Benyamin Guluh Kolaka: Relationship between Experience and Length of Stay with Anxiety in Children Undergoing Hospitalization in the Inpatient Room at Benyamin Guluh Kolaka Hospital - Reski Ika Patantan; I Wayan Romantika; Narmawan Narmawan; Amzal Mortin Andas (Jurnal Surya Medika (JSM), 2022)
Hospitalization that occurs in children is an experience that interferes with children's lives which can also cause anxiety in children. Stress due to hospitalization will cause feelings of discomfort that can interfere with the treatment process. This study aims to determine the relationship between the treatment experience and the length of stay with anxiety in hospitalized children. This study used a cross-sectional study design with a total sample of 44 pediatric patients aged 3-6 years who were taken by purposive sampling. The research data were analyzed using Fisher's exact statistical test. The results showed no relationship between the treatment experience, p-value = 0.702, and the anxiety of children undergoing hospitalization. There is a relationship between the length of stay, p-value = 0.045, with anxiety in children undergoing hospitalization.